2005
DOI: 10.1007/s00384-005-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan, an endothelin receptor antagonist, reduces leucocyte adhesion and inflammation in a murine model of inflammatory bowel disease

Abstract: Bosentan reduces the adhesion of leucocytes in colonic submucosal venules and reduces inflammation in this mouse model of IBD. By inhibiting leucocyte adhesion, a crucial step in the recruitment of leucocytes to the inflamed tissue, bosentan is a potent therapeutic drug in this animal model. Further studies are necessary to investigate the role of bosentan as a novel drug in human IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…It is more likely that chronic treatment with bosentan suppresses a distinct ET A/B receptor mediated process that develops during CH. In this regard, it is interesting that bosentan acting via ET receptors is a potent anti-inflammatory drug (2,12,16). Indeed, multiple studies in other tissues have shown that ET peptides are multifunctional proinflammatory agents capable of initiating and promoting an immune response.…”
Section: Discussionmentioning
confidence: 97%
“…It is more likely that chronic treatment with bosentan suppresses a distinct ET A/B receptor mediated process that develops during CH. In this regard, it is interesting that bosentan acting via ET receptors is a potent anti-inflammatory drug (2,12,16). Indeed, multiple studies in other tissues have shown that ET peptides are multifunctional proinflammatory agents capable of initiating and promoting an immune response.…”
Section: Discussionmentioning
confidence: 97%
“…This observation provides insight into the mechanism of bosentan as an inhibitor of the inflammatory reaction. In a murine model of inflammatory bowel disease, the antiinflammatory effect of bosentan was investigated, and it was determined that bosentan reduced inflammation in this animal model (Anthoni et al, 2006). In another study, it was seen that prophylactic oral administration of bosentan reduced clinical inflammation in trinitrobenzene sulphonateinduced colitis in rats (Güllüoglu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Three cycles were completed (30 days). This strategy leads to a reliable and reproducible chronic colitis (3,9).…”
Section: Methodsmentioning
confidence: 99%